Karakter Morfofisiologi Daun dan Hasil Kedelai (Glycine max L. Merill) Varietas Petek dan Varietas Jayawijaya pada Naungan - Soverda, Nerty; Alia, Yulia (Jurnal Agro Teknologi Tropika, 2014)
This research aims to study the effect of shade on morphophysiology character and results of soybean Petek andJayawijaya varieties. The study was conducted at the experimental site of Faculty of Agriculture, University of Jambi.Materials and tools used are paranet 50%, soybean seed Petek variety (shade tolerant) and Jayawijaya variety (shadesensitive), manure, NPK fertilizer, fungicide and insecticide. Equipment used includes field equipment, clear nail polish,microscope camera, analytical scales, tweezers and others. This study used a split plot design consisting 2 factors. Thefirst factor is the shade as the main plot (N) which consists of two levels, namely the auspices of 0 % (no shade) and 50% of shade. The second factor (subplot) is soybean varieties are Petek variety and Jayawijaya variety. The resultsshowed that the Petek showed consistency as shade-tolerant variety in shade 50% to show the state of the leaves arethinner, wider leaves, a decrease in stomatal density is lower and higher chlorophyll content compared with Jayawijayavariety (shade sensitive). There is no interaction between treatment shade and variety.